Digital Papillary Adenocarcinoma: Case of a Rare Malignant Cutaneous Tumor of the Eccrine Sweat Gland - Austin J. Jabbour; Ibrahim A. Tangoren; Andrew B. Kanik (Karger Publishers, 2021)
Digital papillary adenocarcinoma (DPA) is a rare cutaneous tumor originating from the eccrine sweat glands. These lesions occur almost exclusively on the digits of the hands and feet, where there is a high concentration of eccrine glands. The diagnosis is made histologically, and the course of the malignancy tends to be very aggressive with high rates of recurrence and early metastasis at the time of diagnosis. Due to the low incidence of these lesions, there have been minimal objective data from clinical studies to recommend specific treatment strategies. Wide local excision versus digital amputation proximal to the lesion has been debated for primary treatment, while there are no data to support routine implementation of adjuvant chemotherapy or radiation, despite its metastatic nature. This article presents a case of long-standing, previously undiagnosed DPA. The lesion appeared more inconspicuous on gross examination than other reports in the literature, and diagnosis was made with punch biopsy and confirmed postsurgically. To date, the patient has not had recurrence, although she is being monitored for potential metastatic deposits in her lungs. Clinical dermatologists should be aware of the high mortality burden this lesion may inflict if left undiagnosed or mistreated.